Enhanced nematic and antiferromagnetic phases in the spin-fermion model for strained iron pnictides - Minghui Qin; Shuai Dong; Junming Liu; Zhifeng Ren (New Journal of Physics, 2015)
The effects of anisotropic superexchange and Fe–Fe hoppings on phase transitions in the undoped three-orbital spin-fermion model are investigated to understand the experimentally reported strain effect in BaFe _2 As _2 . Monte Carlo simulated phase diagrams show that both the collinear antiferromagnetic and nematic transitions shift toward high temperature with the increasing magnitude of anisotropies, qualitatively consistent with experimental observation. Thus, both the anisotropic superexchange and Fe–Fe hoppings are suggested to be responsible for the variation of the transition temperatures of BaFe _2 As _2 with uniaxial stress. In addition, we observed a 90 degree rotation of the collinear antiferromagnetic order, accompanied with a reversal of the orbital occupancy at the Fermi surface when the sign of the superexchange anisotropy changes, further supporting previous predictions by first principles calculation.